2020
DOI: 10.21203/rs.3.rs-37115/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zadek osteotomy for the treatment of Haglund’s Syndrome

Abstract: Background Although several treatment options described in paper, Haglund’s Syndrome (HS) is a challenging common lower extremity disorder. This study reported the clinical outcomes of Zadek osteotomy (ZO) for the treatment of HS. Methods This retrospective study included 19 patients who underwent ZO from January 2016 to June 2018. Patients were evaluated using the American Orthopedic Foot Ankle Society ankle-hindfoot scale (AOFAS), Visual Analogue Scale (VAS), ankle range of motion (AROM), and Chauveaux-Lie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Three studies were published abstracts and 14 of which were full-length publication. 6,7,10 -12,14,22 -24,26,28,33,34,37,38,43,45 A total of 611 subjects and 625 procedures were found in these 17 studies; 81 procedures were percutaneous, and 544 procedures were open. The mean age of patients who underwent percutaneous ZO was 49.6 (range 37.4-57), and the mean age of the patients who endured open ZO was 47.65 (range 32.5-54.7).…”
Section: Methods and Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were published abstracts and 14 of which were full-length publication. 6,7,10 -12,14,22 -24,26,28,33,34,37,38,43,45 A total of 611 subjects and 625 procedures were found in these 17 studies; 81 procedures were percutaneous, and 544 procedures were open. The mean age of patients who underwent percutaneous ZO was 49.6 (range 37.4-57), and the mean age of the patients who endured open ZO was 47.65 (range 32.5-54.7).…”
Section: Methods and Search Strategymentioning
confidence: 99%
“…4,28 ZO was first described as an open surgery; similar to other open foot and ankle surgeries, this technique has been associated with complications such as nerve injuries and wound healing issues. 7,[12][13][14]18,22,37,38,44,45 However, in light of new, minimally invasive surgery (MIS) techniques, the ZO can be completed percutaneously. The percutaneous ZO is chosen with the intention of decreasing risks of complications commonly observed with the open ZO, while also allowing for earlier weightbearing and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the effectiveness and safety of ZO in treating HD and IAT ( Tables 1 and 2 ). 8 , 12 , 20 , 22 , 34 , 40 , 49 , 66 , 67 , 78 Zhang et al 77 demonstrated improved VAS and AOFAS scores and no complications at a mean of 3.1 years of follow-up for the treatment of HS. VAS scores significantly improved from a preoperative mean of 7.23 to 0.43; AOFAS scores also significantly improved from 50.60 to 94.27.…”
Section: Treatmentmentioning
confidence: 99%